2007
DOI: 10.1007/s00436-007-0662-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in Hysterothylacium aduncum, a raphidascarid nematode isolated from sprat (Sprattus sprattus) of different geographical areas of the northeastern Atlantic

Abstract: Species of the genus Hysterothylacium are among the most common marine nematode fish parasites in the northern Atlantic. Due to recent findings of cryptic speciation in other parasitic ascaridoid nematodes, a similar pattern of sibling species was hypothesized also for Hysterothylacium aduncum. By investigating a 886- to 890-bp-long genomic DNA fragment including ITS-1, 5.8S rDNA and ITS-2 of 40 specimens of H. aduncum of sprat (Sprattus sprattus) of four different biogeographical regions (North Sea, English C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
(32 reference statements)
5
19
0
Order By: Relevance
“…by Paraguassú et al (2002). In species of Hysterothylacium, the excretory pore is located in the region of the nerve ring, thus differing from species of Contracaecum, in which it is located near the ventral interlabia (DEARDORFF; OVERSTREET, 1981;RUKERT., 2005;KLIMPEL et al, 2007;KNOFF et al, 2012;BORGES et al, 2012). According to Smith and Wooten (1978), although it is difficult to identify species based on morphological characters alone, it is even more difficult in relation to the larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…by Paraguassú et al (2002). In species of Hysterothylacium, the excretory pore is located in the region of the nerve ring, thus differing from species of Contracaecum, in which it is located near the ventral interlabia (DEARDORFF; OVERSTREET, 1981;RUKERT., 2005;KLIMPEL et al, 2007;KNOFF et al, 2012;BORGES et al, 2012). According to Smith and Wooten (1978), although it is difficult to identify species based on morphological characters alone, it is even more difficult in relation to the larval stages.…”
Section: Discussionmentioning
confidence: 99%
“…the data only include positive hits. Studies that set out to search for cryptic helminth species but found none do exist [18], but are probably under-represented in the literature. It is therefore difficult to determine the frequency at which one described taxon consists of cryptic species, and all inferences rest solely on cases where cryptic species have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The larvae were then identified according to morphological features (Yoshinaga et al 1987, Petter & Maillard 1988. No molecular techniques were needed, since no cryptic sibling species were detected by Klimpel et al (2007). Next, a number of larvae were frozen (-80°C) for enzyme determination (L3-0h).…”
Section: Methodsmentioning
confidence: 99%